Split-bolus computed tomography urography (CTU) achieves more than half of radiation dose reduction in females and overweight patients than conventional single-bolus computed tomography urography - Wang, Li-Jen (Transl Oncol, 2021)
OBJECTIVE: To compare radiation dose between single-bolus and split-bolus computed tomography urography (CTU). MATERIALS AND METHODS: We prospectively enrolled patients undergoing single-bolus and split-bolus CTU from 2019 June to 2020 June. The age, sex and body mass index (BMI) of each patient was recorded and categorized into BMI classes. The radiation dose indices including volumetric computed dose index, size-specific dose estimate, dose length product and effective dose of each patient were compared between 2 CTU groups with calculation of dose reduction proportions (DRPs). RESULTS: Seventy-six patients underwent single-bolus (n = 39) and split-bolus (n = 37) CTU. Single-bolus CTU had higher radiation doses than split-bolus CTU and there were statistically significant differences of all radiation dose indices between two CTU groups without and with stratification by sex and BMI classes. The DRPs of volumetric computed dose index, size-specific dose estimate, dose length product and effective dose using split-bolus CTU were 49%, 49%. 50%, and 45%, respectively. Multiple linear regression with an effect size (f(2)) as 2.24 showed females (p = 0.027) and higher BMI classes (p = 2.38 *10(−9)) were associated with higher effective doses; and split-bolus CTU, lower effective doses (p = 5.40 *10(−15)). Using split-bolus CTU, females had consistently higher DRP of all radiation dose indices than males (54–55% versus 40–42%). Overweight patients had the largest DRP as 55% of effective dose. CONCLUSIONS: Split-bolus CTU could be preferred by its significant radiation dose reduction effect in regard to single-bolus CTU, which was most profound in females and overweight patients.